Case report: Refractory focal motor seizure associated with cerebrospinal fluid neurochondrin antibody - Ahmad, Rowaid; Huang, Yumeng; Wang, Peter R.; Masel, Todd; Li, Xiangping (Frontiers in Immunology, 2024)
Background Focal onset seizures, characterized by localized neuronal hyperexcitability in the brain, can be related to various structural, immune, genetic, or metabolic abnormalities. Autoimmune epilepsies are increasingly recognized. Neurochondrin antibody has been reported in a variety of rare autoimmune neurological disorders. This article aims to highlight the relevance of anti-neurochondrin in autoimmune epilepsy. Methods This is a case presentation and literature review of autoimmune epilepsy associated with anti-neurochondrin antibody. Case presentation A 26-year-old African American right-handed man with a history of Sjogren’s syndrome presented with near constant, rhythmic left-sided facial twitching movements, and one episode of generalized tonic clonic seizure. Magnetic resonance imaging (MRI) of the brain revealed borderline low volume right hippocampus. Cerebrospinal fluid (CSF) studies yielded elevated protein and mild lymphocytic pleocytosis. Antibody Prevalence in Epilepsy 2 (APE2) score was 6, and autoimmune workup was initiated. Anti-neurochondrin antibody returned positive in the CSF autoimmune encephalitis panel with a titer of 1:512 (Mayo Clinic TEST ID: ENC2). Seizures remained refractory to anti-seizure medications including divalproex, lacosamide, and oxcarbazepine. Immunotherapy with methylprednisolone and immunoglobulin improved his epileptic seizures. Conclusion This is the first reported case of refractory autoimmune epilepsy with positive CSF anti-neurochondrin antibody. This study contributes to the body of evidence supporting the role of neurochondrin antibody in epilepsy. Considering autoimmune testing in individuals with seizures having APE2 score > 4 can aid in timely diagnosis of immune-mediated epilepsy and initiation of immunotherapy, which can result in favorable clinical outcomes. Diagnosis of autoimmune epilepsy, in most cases, is based on clinical characteristics, MRI results, and CSF findings. In addition to the traditional antibody panel for autoimmune encephalitis, some novel antibodies, such as anti-neurochondrin, should also be considered.